2017
DOI: 10.1038/srep46228
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a variant-specific phosphorylation of TH2A during spermiogenesis

Abstract: Tissue-specific histone variant incorporation into chromatin plays dynamic and important roles in tissue development. Testis is one such tissue, and a number of testis-specific histone variants are expressed that have unique roles. While it is expected that such variants acquire post-transcriptional modifications to be functional, identification of variant-specific histone modifications is challenging because of the high similarity of amino acid sequences between canonical and variant versions. Here we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…H4S1 phosphorylation has been found to be essential for chromatin compaction and concomitantly histone accessibility (Krishnamoorthy et al, 2006; Wendt and Shilatifard, 2006), suggesting that H4S1 phosphorylation is required for histone replacement during spermiogenesis. Outside the canonical histones, many phosphorylated residues have been identified, using mass spectrometry analyses, that exist on different testis-specific histone variants, such as H1T, HILS1, TH2A, TH2B (Sarg et al, 2009; Pentakota et al, 2014; Mishra et al, 2015; Luense et al, 2016; Hada et al, 2017). Although many core histones and histone variants phosphorylation have been identified in germ cells, their physiological roles need further investigation.…”
Section: Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…H4S1 phosphorylation has been found to be essential for chromatin compaction and concomitantly histone accessibility (Krishnamoorthy et al, 2006; Wendt and Shilatifard, 2006), suggesting that H4S1 phosphorylation is required for histone replacement during spermiogenesis. Outside the canonical histones, many phosphorylated residues have been identified, using mass spectrometry analyses, that exist on different testis-specific histone variants, such as H1T, HILS1, TH2A, TH2B (Sarg et al, 2009; Pentakota et al, 2014; Mishra et al, 2015; Luense et al, 2016; Hada et al, 2017). Although many core histones and histone variants phosphorylation have been identified in germ cells, their physiological roles need further investigation.…”
Section: Phosphorylationmentioning
confidence: 99%
“…During the nuclear chromatin re-organization in spermiogenesis, the majority of the somatic histones are firstly replaced by testis-specific histone variants, and transition proteins (TPs) are subsequently incorporated in the nuclei of spermatids, protamines (PRMs) further replace TPs in the late spermatids to pack the genome into the highly condensed sperm nucleus (Rathke et al, 2014; Bao and Bedford, 2016). During the histone-to-protamine transition, the histone variants and specific histone modifications play essential roles by modulating the chromatin compaction and higher-order chromatin structure ( Table 1 ) (Boskovic and Torres-Padilla, 2013; Bao and Bedford, 2016; Hada et al, 2017; Hao et al, 2019). Defects in either the replacement or the modification of histones might result in azoospermia, oligospermia or teratozoospermia, which leads to male infertility ( Table 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Along with histone H4 acetylation at multiple sites, other PTMs occur on histones prior to their turn-over, such as methylation, phosphorylation, crotonylation and ubiquitinylation of histone H3 and H2B residues (Wendt and Shilatifard, 2006 ; Govin et al, 2010 ; Lu et al, 2010 ; Tan et al, 2011 ; Brunner et al, 2014 ; Dottermusch-Heidel et al, 2014a , b ; Pentakota et al, 2014 ; Rathke et al, 2014 ; Mishra et al, 2015 ; Hada et al, 2017 ; Hoghoughi et al, 2017 ). Some of them are transmitted to the embryo via the persisting histones; their role and effect remain to be determined.…”
Section: Sperm Chromatinmentioning
confidence: 99%
“…The defects observed could therefore be due to an inappropriate chromatin structure and subsequent genome disorganization, rather than to a specific action of TH2A or TH2B (16). In agreement with this hypothesis, two recent reports showed that TH2A could be phosphorylated at the TH2A-specific Thr127 and that this phosphorylation is dispensable for normal spermatogenesis and male fertility (17,18).…”
Section: Th2bmentioning
confidence: 57%